Microbiota as key factors in inflammatory bowel disease - White, Zachary; Cabrera, Ivan; Kapustka, Isabel; Sano, Teruyuki (Frontiers in Microbiology, 2023)
Inflammatory Bowel Disease (IBD) is characterized by prolonged inflammation of the gastrointestinal tract, which is thought to occur due to dysregulation of the immune system allowing the host’s cells to attack the GI tract and cause chronic inflammation. IBD can be caused by numerous factors such as genetics, gut microbiota, and environmental influences. In recent years, emphasis on commensal bacteria as a critical player in IBD has been at the forefront of new research. Each individual harbors a unique bacterial community that is influenced by diet, environment, and sanitary conditions. Importantly, it has been shown that there is a complex relationship among the microbiome, activation of the immune system, and autoimmune disorders. Studies have shown that not only does the microbiome possess pathogenic roles in the progression of IBD, but it can also play a protective role in mediating tissue damage. Therefore, to improve current IBD treatments, understanding not only the role of harmful bacteria but also the beneficial bacteria could lead to attractive new drug targets. Due to the considerable diversity of the microbiome, it has been challenging to characterize how particular microorganisms interact with the host and other microbiota. Fortunately, with the emergence of next-generation sequencing and the increased prevalence of germ-free animal models there has been significant advancement in microbiome studies. By utilizing human IBD studies and IBD mouse models focused on intraepithelial lymphocytes and innate lymphoid cells, this review will explore the multifaceted roles the microbiota plays in influencing the immune system in IBD.